PERENCANAAN PEMBANGUNAN DESA DI DESA BAGAN LIMAU KECAMATAN UKUI KABUPATEN PELALAWAN - Pislawati Alfiaturrahman (UIR Press, 2016)
This study is a qualitative study with the primary objective or describe in detail and depth ofcommunity participation in development planning in the village of the District baganlimau UkuiPelalawan. This is a descriptive study with inductive approach. Of the research concluded:Development Planning Process has not been implemented properly in the village BaganLimau,where several stages of development in the village planning process BaganLimau not beenimplemented, including the stages of preparation and discussion phase activities / prioritizationof activities that will be submitted to the District Musrenbang level. musrenbang at the districtlevel a few stages of the planning process has not been implemented, especially at the stagewhere people have not been involved to decide the priority activities to be submitted to the levelof the District. Community participation in development planning in the village BaganLimauDistrict of Ukui Pelalawan still low for it is necessary to improve the implementation stages ofparticipatory planning, optimize the identification of problems and needs of the community, andthe need to increase understanding of the village , the building blocks and the public ondevelopment planning.